Study of Socioeconomic Conditions of Farmer Households After Wood Processing Industry Development In Talang Kelapa District, Banyuasin Regency - Arbi, Muhammad; Junaidi, Yulian; Januarti, Indri; Sherly, Sherly (Eduvest - Journal of Universal Studies, 2023)
One of the impacts of industrial activities is that it provides regional economic progress, especially contributing to the value of regional GDP. This research uses a survey method through observation and interviews as well as literature study and is presented descriptively analytically. The results of this research show that in terms of the perception of farmer households living around the timber industry location as measured by indicators of the company's presence in terms of infrastructure and environment, social relations and employment opportunities, it shows the medium category with a score of 32.74. One of the reasons for this is the increase in the number of migrant residents and the increase in the allocation of working hours to earn a living. Judging from the economic aspect, it is known that the average economic household of farmers living around the location of wood industry activities has an income of around IDR 2,180,540 per month, while the average living needs (DLN) in the area is IDR 3,000,914. - per month or minus Rp. 820,374,- per month. The contribution of income from working as a laborer in a wood factory to the total income of farmer households is 67.35%. This means that the influence of the presence of timber companies in the community is quite a positive contribution to the economy of the surrounding community. However, the company's existence also raises environmental issues, including the potential for disruption to physical-chemical and socio-cultural components as well as public health.